Migration by sea: protection of asylum seekers - Farah Nurul Ayu Izany; Rohani Abdul Rahim; Annalisa Yahanan; Azizah Landa (Penerbit Universiti Kebangsaan Malaysia, 2019)
Protection of asylum seekers migrating by sea are reflected in international law on refugees, international maritime law, international human rights and international criminal law. Asylum seekers shared their mode of travel via sea with many types of migrant, and most of the time they are being referred to as “mixed migration” or “irregular maritime migration” or “boat people”. They have the rights to family life and basic needs and assistance for shelter, food, legal, medical and psychosocial assistance from the UNHCR and the relevant organizations. The right also includes the right to seek and to enjoy protection from persecution(Article 14 of the Universal Declaration of Human Rights) in other countries of asylum. The asylum seeker may be recognized as a refugee when the person’s circumstances fall into the definition of “refugee” according to the 1951 Convention relating to the Status of Refugees (1951 Convention) or other refugee laws. The issues of asylum seekers migrating by sea are complex as a result of conflicts between provisions of different international legal regimes. Aiding those in peril at sea is an obligation codified under several conventions relating to international maritime law such as the United Nations Convention on the Law of the Sea of 1982 (UNCLOS), the International Convention for the Safety of Life at Sea of 1974 (SOLAS) as amended, the International Convention on Maritime Search and Rescue of 1979 (SAR) as amended, and the 1958 Convention on the High Sea (to the extent that it has not been superseded by UNCLOS). Therefore, this write up examines provisions from different strands of international law that bear asylum seekers who are migrating by sea which includes the scope of search and rescue, and disembarkation of asylum seeker on coastal States. Simultaneously it also attempts to explore Malaysia attitudes towards asylum seekers migrating by sea.